2017
DOI: 10.1007/s00415-017-8391-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin: 80 years young, from epilepsy to breast cancer, a remarkable molecule with multiple modes of action

Abstract: In 1908 phenytoin (5,5-diphenylhydantoin) was first synthesized as a barbiturate derivative in Germany by professor Heinrich Biltz (1865-1943) and subsequently resynthesized by an American chemist of the pharmaceutical company Parke-Davis in 1923 in Detroit. Screening phenytoin did not reveal comparable sedative side effects as barbiturates and, thus, Parke-Davis discarded this compound as a useful drug. In 1936, phenytoin's anticonvulsive properties were identified via a new animal model for convulsive disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…21,54 This fact could be explained by differences in the selectivity and the pharmacokinetics profile of both compounds. 52 Our results provide us the opportunity for further structural optimization based on the interactions with Nav1.2 proposed by molecular modeling. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 24 4.1.1 Construction of Nav1.2.…”
Section: Discussionmentioning
confidence: 76%
“…21,54 This fact could be explained by differences in the selectivity and the pharmacokinetics profile of both compounds. 52 Our results provide us the opportunity for further structural optimization based on the interactions with Nav1.2 proposed by molecular modeling. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 24 4.1.1 Construction of Nav1.2.…”
Section: Discussionmentioning
confidence: 76%
“…Although many patients were responders to compounded creams containing for example amitriptyline, ketamine, and baclofen, a number of patients remained treatment-resistant. We therefore introduced phenytoin as a new compound for topical neuropathic pain treatment based on its remarkable history and its various modes of action [ 15 , 16 , 17 ]. Phenytoin, as a broad-acting ion channel blocker with neuroprotective and anti-inflammatory properties, seemed to be an optimal choice as an effective compound that is able to modulate peripheral mechanisms, which are increasingly recognized as important drivers in neuropathic pain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 3) [51]. we also found that phenytoin can augment the analgesic effects of other (co-)analgesics [52].…”
Section: Phenytoin Cream Formulation Repositioning Strategymentioning
confidence: 54%